Literature Review: Pengaruh Jahe Terhadap Skala Nyeri Pada Lansia Dengan Artritis Gout - Prabasari, Ninda Ayu (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2019)
Introduction: The aging process results in a disturbance in purine metabolism that triggers gout arthritis. The symptoms appear in the joints including swelling, redness, and heat, resulting in stiffness and pain at night. Pain occurs continuously can cause a decrease in the elderly quality of life. The objective of the literature review is review the effectiveness of ginger on the pain scale in the elderly with Gout Arthritis. Method: Literature review was conducted based on issues, methodology and outcome equations. The study used a total of 11 research using quantitative studies, pre-experimental designs using or without a control group. The variable used pain scale in patients with Gout Arthritis. Results: Ginger interventions were obtained 9 research used ginger as a compress and 2 other research used ginger as a foot soak. There are 2 researchs whose results are not different but showed the effectiveness of ginger against pain reduction in the elderly who experience gout arthritis. The first study compared therapeutic warm water baths with warm ginger baths and the second study compared white ginger compresses with grated ginger compresses. Overall research shows the effectiveness of ginger against pain reduction. Discussion: Ginger can be used as an alternative intervention to reduce pain in the elderly with Athritis Gout.